Advanced Innovation Management Best Practice of German and American Corporations in the Mobility Sector - Hirte, Rebecca; Roth, Philip (Journal of Strategic Innovation and Sustainability, 2018)
Many established corporations are currently seeking to adapt their business models and innovation frameworks in order to compete with disruptive businesses. In this context, semi-structured qualitative expert interviews (n=19) have been conducted in Germany and the USA, which examine advanced approaches of innovation management. Results include the need to build up technology driven competencies within the corporation, as well as advanced incentive schemes. Further detected findings refer to the funding of innovation projects, cooperation with external partners, and internal structures. Presented recommendations will help corporations to fine tune their innovation activities by learning from insights into various multinational firms.